2016
DOI: 10.1093/pm/pnw078
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Perspectives on Tapering of Chronic Opioid Therapy: A Qualitative Study

Abstract: OBJECTIVE : There is inadequate evidence of long-term benefit and growing evidence of the risks of chronic opioid therapy (COT). Opioid dose reduction, or opioid tapering, may reduce these risks but may also worsen pain and quality of life. Our objective was to explore patients' perspectives on opioid tapering. DESIGN : Qualitative study using in-person, semistructured interviews. SETTING AND PATIENTS : English-speaking, adult primary care patients (N = 24) in three Colorado health care systems. METHODS : Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
133
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(140 citation statements)
references
References 38 publications
6
133
0
1
Order By: Relevance
“…To alleviate or avoid the aversive symptoms of withdrawal, many of these individuals continue to use opiates [1][2][3][4] . Withdrawal is therefore a key determinant of opiate use in dependent individuals, yet its underlying mechanisms are poorly understood and effective therapies are lacking.…”
mentioning
confidence: 99%
“…To alleviate or avoid the aversive symptoms of withdrawal, many of these individuals continue to use opiates [1][2][3][4] . Withdrawal is therefore a key determinant of opiate use in dependent individuals, yet its underlying mechanisms are poorly understood and effective therapies are lacking.…”
mentioning
confidence: 99%
“…For example, when doctors showed genuine concern for their patients’ health and well-being, patients with chronic pain seemed more willing to accept decisions to limit or deny opioids. 22 In a recent study involving interviews with patients being tapered off of opioids, Frank and colleagues 13 reported that patients believed having a trusted physician was essential. Studies have shown that when patients and their PCPs have similar concerns about opioids, they can approach these concerns collaboratively.…”
Section: Discussionmentioning
confidence: 99%
“…4,16,23 Collaboration and trust are especially important as nonopioid treatments are explored and as patients face fears of opioid withdrawal or uncontrolled pain. Indeed, in Frank and colleagues’ 13 interviews, patients revealed that withdrawal and uncontrolled pain were major barriers to opioid tapering. Further corroborating the importance of provider support during opioid tapering, a recent pilot study reported that patients randomized to a taper support intervention involving psychiatric consultation and weekly meetings with a physician assistant showed greater improvement on pain interference, pain self-efficacy, and perceived opioid problems, than control patients.…”
Section: Discussionmentioning
confidence: 99%
“…Los riesgos potenciales incluyen los síntomas por síndrome de abstinencia, incremento del dolor y pérdida de seguimiento (15). Sin embargo, algunos pacientes informaron mejoras en la función y calidad de vida después de la disminución (16). Los efectos de la disminución de la dosis de opiodes y los resultados en los pacientes no han sido sistemáticamente revisados.…”
Section: Sr Directorunclassified